Facies analysis of the Codó Formation (Late Aptian) in the Grajaú Area, Southern São Luís-Grajaú Basin - Rossetti,Dilce F. (2004)
Facies descriptions of the Codó Formation in the Grajaú area are provided for the first time, and its sedimentary characteristics compared to those from the Codó area to allow paleoenvironmental reconstructions. Deposits in the Grajaú area include evaporites, limestones and argillites bearing features indicative of a shallow, low energy, subaqueous, saline environment exposed to meteoric and/or capillary conditions. Flooding-evaporative concentration-desiccation cycles suggest a saline pan complex surrounded by extensive evaporitic mudflats. The location of the system, whether coastal or inland, is a matter open for debate. However, the later hypothesis is favored considering: 1. Sr isotopic data, with values higher than those expected for Late Aptian marine waters; 2. calcitic composition of limestones (instead of dolomitic and/or magnesitic as expected in coastal settings); and 3. presence of continental ostracods and lack of marine fauna. This interpretation is consistent with that proposed for UpperAptian deposits of the Codó area, but the depositional system there was one dominated by more stable, well-stratified, anoxic waters and evaporite precipitation in central lacustrine areas, while in the Grajaú area the salt pan was more oxygenated and ephemeral, with salt precipitation mainly in marginal areas or along surrounding mudflats.